Collapsing Pattern Class-IV Lupus Nephritis Presenting as Posterior Reversible Encephalopathy Syndrome and Cardiac Tamponade: A Rare COVID-19 Sequelae - K Harshitha Reddy; Pranjal Kashiv; Sunil Kumar; Sourya Acharya; Kapil Navin Sejpal (Journal of Clinical and Diagnostic Research)
One of the most detrimental and severe presentations of Systemic Lupus Erythematosus (SLE) is Lupus Nephritis (LN), which is a type of glomerulonephritis. Type-IV Lupus Nephritis, or diffuse Lupus Nephritis, is a severe illness characterised by diffuse proliferative lesions. In this setting, the prognosis worsens if cellular crescent is present. It is divided into two types: diffuse segmental and the other being diffuse global. Wire-loop lesions could also be observed. There have been reports of Collapsing Glomerulopathy (CG) in SLE patients with Focal Segmental Glomerulosclerosis (FSGS). The collapsing variety of FSGS (cFSGS) is defined histopathologically by segmental or global glomerular capillary condensation and obliteration, the appearance of hyperplastic and hypertrophic podocytes, and substantial tubulointerstitial damage. Numerous aetiologies have been proposed, including viral infections such as Human Immunodeficiency Virus (HIV), Cytomegalovirus (CMV), Epstein-Barr virus, and Parvovirus B19, as well as medications and acute ischaemia. Patients infected with Coronavirus Disease-2019 (COVID-19) have an increased risk of acute renal injury as there is a systemic inflammatory cascade due to an acute infection, causing impairment of basic cellular activities in podocytes. Hereby, the authors present a case report of a 17-year-old female who experienced cardiac tamponade and seizures due to Posterior Reversible Encephalopathy Syndrome (PRES). Further investigation and kidney biopsy revealed she had lupus nephritis Stage-IV Diffuse Proliferative Glomerulonephritis (DPGN) but with the collapsing variety, which is a rare finding. Additionally, the patient tested positive for COVID-19, which may have contributed to the development of the collapsing type of DPGN.